2010
DOI: 10.3109/00016480903161541
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of diagnostic approaches to idiopathic sudden sensorineural hearing loss and their influence on treatment and outcome

Abstract: Methods:The first 400 patients submitted to the Swedish national database for SSNHL were analyzed. Information was collected at the first visit about the patient's past medical history, potential precipitating events traumata, family medical history, hearing loss, current disease, diagnostic protocol and treatment using questionnaires as well as two audiograms for each patient, one at the first visit to the ENT-clinic and one three months later.Results: 65% of these 400 patients underwent hematological tests a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 17 publications
1
38
1
Order By: Relevance
“…A recent study of practice patterns in Sweden found that all of the 400 patients with SSNHL in the study had standard audiography, but only 65% and 40% underwent laboratory testing or MRI imaging, respectively, even when treated by otolaryngologists (Nosrati-Zarenoe et al, 2010). In comparison, a recent review of the diagnostic evaluation of 128 patients presenting with SSNHL presenting to a major U.S. medical center revealed the average number of diagnostic tests they received was six.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A recent study of practice patterns in Sweden found that all of the 400 patients with SSNHL in the study had standard audiography, but only 65% and 40% underwent laboratory testing or MRI imaging, respectively, even when treated by otolaryngologists (Nosrati-Zarenoe et al, 2010). In comparison, a recent review of the diagnostic evaluation of 128 patients presenting with SSNHL presenting to a major U.S. medical center revealed the average number of diagnostic tests they received was six.…”
Section: Discussionmentioning
confidence: 99%
“…The sensitivity and specificity of MRI with gadolinium in the diagnosis of vestibular schwannoma is nearly 100% for tumors over 3 mm in diameter (Cueva, 2004;Fortnum et al, 2009). A total of 1% to 6% of patients with SSNHL on average will have positive findings on MRI (Chaimoff, Nageris, Sulkes, Spitzer, & Kalmanowitz, 1999;Chau et al, 2010;Fetterman et al, 1996;Fitzgerald & Mark, 1998;Nosrati-Zarenoe et al, 2010;Tucci et al, 2002). Contraindications to use of gadolinium include glomerular filtration rate <30 mL/min and nephrogenic systemic fibrosis (Thomsen, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[5,13] Auditory data were also classified according to the configuration of the audiogram into six subgroups including ascending type (hearing loss at 250-500 Hz), descending type (hearing loss at 4000-8000 Hz), flat type (hearing loss with a 10 dB or less difference between the best and worst thresholds), total and near-total (85 dB and above), cookie bite and reverse cookie bite hearing losses. [4,5,14,15] The patients were also classified according to their age as 7-40 years, 41-53 years and 54-87 years. [16] The patients were divided into two groups by the receiver operating characteristic (ROC) analysis method as those treated within the first three days and those treated after three days.…”
Section: Methodsmentioning
confidence: 99%